The complex approach to the project team building - Чумаченко, Игорь Владимирович; Доценко, Наталья Владимировна; Сабадош, Любомир Юрьевич (Eastern-European Journal of Enterprise Technologies, 2012)
Application of the complex approach to the project team building is considered. The process is described and the method of team building is offered taking into account restriction on roles combination